Transcontinental migratory connectivity predicts parasite prevalence in breeding populations of the European barn swallow. (26th February 2015) - von Rönn, J. A. C.; Harrod, C.; Bensch, S.; Wolf, J. B. W.
Abstract Parasites exert a major impact on the eco‐evolutionary dynamics of their hosts and the associated biotic environment. Migration constitutes an effective means for long‐distance invasions of vector‐borne parasites and promotes their rapid spread. Yet, ecological and spatial information on population‐specific host–parasite connectivity is essentially lacking. Here, we address this question in a system consisting of a transcontinental migrant species, the European barn swallow (Hirundo rustica) which serves as a vector for avian endoparasites in the genera Plasmodium, Haemoproteus and Leucocytozoon. Using feather stable isotope ratios as geographically informative markers, we first assessed migratory connectivity in the host: Northern European breeding populations predominantly overwintered in dry, savannah‐like habitats in Southern Africa, whereas Southern European populations were associated with wetland habitats in Western Central Africa. Wintering areas of swallows breeding in Central Europe indicated a migratory divide with both migratory programmes occurring within the same breeding population. Subsequent genetic screens of parasites in the breeding populations revealed a link between the host's migratory programme and its parasitic repertoire: controlling for effects of local breeding location, prevalence of Africa‐transmitted Plasmodium lineages was significantly higher in individuals overwintering in the moist habitats of Western Central Africa, even among sympatrically breeding individuals with different overwintering locations. For the rarer Haemoproteus parasites, prevalence was best explained by breeding location alone, whereas no clear pattern emerged for the least abundant parasite Leucocytozoon. These results have implications for our understanding of spatio‐temporal host–parasite dynamics in migratory species and the spread of avian borne diseases.